Exploring Key Drivers Influencing Customer Experience: Evidence from Telecom Companies in the Philippines - Timbang, Marie Anne Rose (Journal of Interdisciplinary Perspectives, 2024)
This study explores the impact of brand image, price, and service quality on customer experience in telecom companies within Clark Freeport Zone, Philippines. Using a stratified sample of 125 respondents, the research employs descriptive statistics, weighted average means, and multiple linear regression for data analysis. The study aims to fill a research gap by examining how these factors affect customer experience, offering unique insights specific to this zone. Findings from Spearman's rho correlation and regression analysis show significant positive relationships between brand image, price, service quality, and customer experience. These factors are confirmed as significant predictors, positively influencing customer experience. The results provide valuable insights for telecom companies in Clark Freeport Zone to enhance customer experience strategies and improve customer satisfaction, loyalty, and acquisition. Addressing these aspects can boost brand perception, reduce customer churn, and promote sustainable business growth.